2006
DOI: 10.1099/mic.0.28771-0
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic stress in Synechocystis sp. PCC 6803: low tolerance towards nonionic osmotic stress results from lacking activation of glucosylglycerol accumulation

Abstract: In order to compare the molecular principles of the acclimatization of bacterial cells to salt and nonionic osmotic stress, the moderately halotolerant cyanobacterium Synechocystis sp. PCC 6803 was challenged by salt (NaCl), and the osmolytes sorbitol and maltose. The physiological response towards each of the three compounds was found to be different. After salt addition, the cell volume remained unchanged, and the accumulation of the osmoprotective compound glucosylglycerol (GG) was observed after activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…During the second phase of cell adaptation, not only the biosynthesis and accumulation of the compatible solute but also an influx of sorbitol into the cells may have occurred. Sorbitol influx has been shown to occur in cells of wild-type Synechocystis and a mutant unable to synthesize the compatible solute glucosylglycerol when they were treated with large amounts of external sorbitol (49). Taken together, these results suggest that the uptake of K ϩ into the cells via K ϩ transporters was required for the first phase of recovery and that Ktr especially but not Kdp contributed significantly to this first recovery phase.…”
Section: Discussionsupporting
confidence: 61%
“…During the second phase of cell adaptation, not only the biosynthesis and accumulation of the compatible solute but also an influx of sorbitol into the cells may have occurred. Sorbitol influx has been shown to occur in cells of wild-type Synechocystis and a mutant unable to synthesize the compatible solute glucosylglycerol when they were treated with large amounts of external sorbitol (49). Taken together, these results suggest that the uptake of K ϩ into the cells via K ϩ transporters was required for the first phase of recovery and that Ktr especially but not Kdp contributed significantly to this first recovery phase.…”
Section: Discussionsupporting
confidence: 61%
“…For example, in Synechocystis sp. PCC 6803, it was shown that the response to solutes used to induce hypertonic (hyperosmotic) stress differs depending on the identity of the solute used (18). Although the same systems are involved in transduction of salt signals and hyperosmotic signals, expression of individual genes is regulated to different extents when using sodium chloride versus sorbitol in this organism (21).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Synechocystis regulates Na ϩ influx and efflux across the plasma membrane and the thylakoid membrane via an Na ϩ transport system, e.g., an Na ϩ /H ϩ antiporter, in order to control ion homeostasis in the cytosol (11,21,33,48). In addition to the Na ϩ cycling system, NaCl also induces synthesis of the osmolyte glucosylglycerol in Synechocystis (27). A reduction in the amount of AqpZ protein was observed during salt stress (Fig.…”
Section: Discussionmentioning
confidence: 95%